Exploring the Role of Leadership Styles in Enhancing Employee Performance : A Meta-Analytic Review (Proceeding of The International Conference on Economics and Business, 2024)
This study examines the effect of different leadership styles transformational, transactional, and laissez-fair on employee performance across various industries. By synthesizing findings from 50 empirical studies, the research provides evidence of the significant impact of transformational leadership on motivation, productivity, and job satisfaction. Practical implications for managerial training are discussed.